Do disability counter-stereotypes humanize the group?: Investigating the role of thinking style - Yu, Janessa Yiyan (Nanyang Technological University, 2022)
Exposure to counter-stereotypes stimulates perceivers to rely less on heuristics and individuate the target, leading to reduced prejudice such as dehumanization. However, holistic thinkers who accept contradictions more than analytic thinkers might be less motivated to engage in this inconsistency resolution process. This research investigated whether the humanizing effect of counter-stereotype exposure extended to the disability context and whether thinking styles moderated this effect. Specifically, I predicted that exposure to disability counter-stereotypes will reduce dehumanization of disability groups and that the effect will be weaker in holistic than analytic thinkers. The main study (N = 162) tested the hypotheses by priming thinking styles, manipulating disability counter-stereotype exposure, and measuring dehumanization towards persons with physical, intellectual, and sensory disabilities. Generally, higher perceived counter-stereotypicality was associated with lower human nature ratings of the target groups, not supporting my first hypothesis. However, this effect was observed in participants primed to think analytically but not holistically, providing partial support for the moderating role of thinking style. These findings suggest that the benefits of counter-stereotype exposure on dehumanization may only occur under certain conditions which can inform future interventions.